Late Holocene Pollen Stratigraphy in Four Northeastern United States Lakes - Gajewski, K.; Swain, A.; Peterson, G. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1987)
ABSTRACTFour pollen diagrams from Maine, New York, and Pennsylvania provide fine resolution (40 or 80 years) records of vegetation change in northeastern United States during the past 2000 years. A long term increase in pollen accumulation rates (PAR) of Picea occurred at the three sites in Maine and New York. Around 1100 years ago, Tsuga and Fagus decreased and Quercus and Castanea increased at Ely Lake in northeastern Pennsylvania. Around 500 years ago, Tsuga and Fagus greatly decreased in Maine and northern New York, while in northeastern Pennsylvania there was an increase in Tsuga and Fagus and a decrease in Quercus and Castanea pollen. Non-arboreal PAR were negligible prior to the European settlement of the area, after which there was an abrupt increase in non-arboreal pollen types.